VERIFICATION OF SOFTWARES FOR ELECTROMAGNETIC FIELD ANALYSIS USING MODELS PROPOSED BY INVESTIGATION COMMITTEES IN IEE OF JAPAN - Takahashi, Norio (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In order to investigate methods for analyzing electromagnetic fields and to compare the accuracy and the CPU time of various codes and so on, investigation committees were set up in IEE of Japan. In this paper, the activities of various investigation committees relating electromagnetic field analysis are described from the viewpoint of the verification of software. [Vol. 12, No. 3 (1997), pp 50-61